Laser biostimulation of seed material Lychnis chalcedonica - Мусина, Р.Т.; Зейниденов, А.К.; Силантьева, М.М. (Fundamental and Experimental Biology, 2023)
The article presents data on the effect of laser irradiation on the viability of the seed material of Lychnis chalcedonica, considers the dynamics of seed germination, and analyzes the morphometric parameters of the seedling. The seed material of the studied species was previously deposited for a day in liquid nitrogen vapor, then exposed to ionizing radiation for 30 seconds, 1, 2, 4 minutes. As a result of the studies, it was found that laser biostimulation leads to an improvement in germination rates by 2.75% compared to the control, i.e. 100 % germination is observed. Seeds begin to germinate on the 2nd day, while in the control on the 3rd day. The morphometric parameters of the seedlings did not change significantly, but turned out to be more viable compared to the control. It is recommended to predeposit the seeds in liquid nitrogen, and then irradiate with a He-Ne laser for 1 or 4 minutes.